Theoretic specific heat from spin wave in comparison with experimental results in Fe-oxide superconductors - Jun, Li; Yu-Feng, Zhang; Zhi-Jie, Qin; Xiao-Li, Niu; Dong-Sheng, Li; Ping-Lin, Li (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Based on the magnetic order of Fe-oxide superconductors from the experiments, we will apply Heisenberg interaction model and analyze systematically the antiferromagnetic configuration with the spin-density-wave, through the strictly mathematical-physical derivation, to suggest the analytic expressions of internal energy and specific heat under the long-wave conditions. The theoretic values show good consistence with the experiments, and both theoretic and experimental results are discussed sufficiently through the phonon contribution to the specific heat, therefore, the spin density wave theory can properly describe the physical characteristics of Fe-oxide superconductors.